O niektórych aspektach funkcjonowania gminy jako jednostki samorządu terytorialnego - Zawierucha, Stefan (On Some Aspects of Gmina's Functioning as a Unit of Local Government, 2007)
The initial point of the article is to determine the functioning of GMINA as a unit of local government in some of its aspects. In the first part the author presents the historical background of the establishment of local government after Poland regained its independence in 1918. Moreover, after the second world war GMINA's reactivation, and later its abolishing through the March Decree as a consequence of the act of the unified organs of the state authorities. Furthermore, the author describes the setting up of GMINA as a unit of local government in 1990. Not only is this part a description of the process of establishing GMINA, but also a presentation of its organs, the determination of its competences and functions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 282-288